PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN PRESTASI BELAJAR MATA PELAJARAN MENGGUNAKAN ALAT-ALAT UKUR (MEASURING TOOL’S) SISWA KELAS X SMK BOEDI OETOMO CILACAP TAHUN 2012/2013 - Rizal Andi Prasetyo (Jurnal Taman Vokasi, 2013)
The objectives of the study were to know the students’ motivation in measuring tool subject by using demonstration method and to know the students’ achievement of measuring tool subject before and after using demonstration method. This study reports that the implementation of demonstration can make the students motivated and active in leaning the material in the class, (2) there was an improvement of the students’ achievement of measuring tool subject, and (3) there was an improvement the students’ motivation in learning measuring tool.